Biofeedback Core Exercise Using Hybrid Assistive Limb for Physical Frailty Patients With or Without Parkinson's Disease - Kotani, Naoya; Morishita, Takashi; Yatsugi, Aya; Fujioka, Shinsuke; Kamada, Satoshi; Shiota, Etsuji; Tsuboi, Yoshio; Inoue, Tooru (Frontiers in Neurology, 2020)
Introduction: Elderly people often exhibit “frailty,” and motor dysfunction occurs. Several studies have reported about the relationship between motor dysfunction and frailty in Parkinson’s disease (PD). This study aimed to test whether the core exercise using the hybrid assistive limb lumbar type for care support (HAL-CB02) may improve the motor functions in frailty patients with or without PD and to explore the optimal patient selection from the frailty cohort. Materials and Methods: We recruited 16 frailty patients (PD=8; non-PD=8). The participants performed core exercise and squats using HAL-CB02 for five sessions a week. Outcome measures were 10-m walking test, step length, timed up and go test, 30-second chair stand test, and visual analog scale. Evaluation was conducted at baseline, post-exercise, and 1- and 3-month follow-ups. Results: Both PD and non-PD patients showed significant improvement in all evaluation items post-exercise. Moreover, no significant difference was found in the improvement value between the two groups. Conclusions: Our results suggest that biofeedback exercise with HAL-CB02 is a safe and promising treatment for frailty patients. Motor dysfunction in PD patients may be partly due to physical frailty, and biofeedback exercise with HAL-CB02 is proposed as a treatment option.